2006
DOI: 10.1111/j.1447-0578.2006.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of matrix metalloproteinases in the pathophysiology of the ovary and uterus

Abstract: Matrix metalloproteinases (MMP) are capable of degrading a variety of extracellular matrix (ECM) proteins and are also involved in the processing of a number of bioactive molecules. Our findings indicate that the functions of MMP in the ovary and uterus are organ-specific and time-dependently vary during the reproductive cycle. Prolactin induces structural luteolysis indicated by loss of luteal weight, protein and DNA within 36 h after pretreatment with ergot alkaloid. MMP activation appears crucial for the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Women habituated to high consumption of AGEs had elevated levels of testosterone, AMH, and androgens [92,109]. High levels of testosterone and androstenedione Irregular menstrual cycles [94][95][96] Raised expression of Receptor of AGE (RAGE) in mononuclear cells along with increased glucose, insulin, and testosterone PCOS characterized as both endocrine metabolic disorders [71,95,97] High AGE diet elevates anti-MĂŒllerian hormone, inhibits Follicle-stimulating hormone Provokes anovulation [98,99] High AGEs isocaloric diet elevates testosterone, insulin, and oxidative stress contributing to PCOS and its symptoms Irregular menstrual cycles, high ovarian cysts [92,97,100] Upregulation of RAGE in PCOS, downregulation signal cascade of steroidogenesis in women of reproductive age Disruptive hormone formation [91,101] Vitamin D3 supplementations reduce the effects of AGEs in PCOS Attenuates AGEs and supports ovarian health [102,103] Excess deposition of collagen Cyst formation in ovaries due to enzyme lysyl oxidase [102,104,105] Disruption of renin-angiotensin-aldosterone system Disturbed cardiovascular functioning and hypertension [37,106,107] Another study reported the association of a high AGE isocaloric diet (HA) with PCOS in women. Women consuming a high HA diet had elevated levels of serum AGEs, testosterone, insulin, and oxidative stress, as compared to women on low AGE isocaloric diet.…”
Section: Ages and Women's Healthmentioning
confidence: 99%
“…Women habituated to high consumption of AGEs had elevated levels of testosterone, AMH, and androgens [92,109]. High levels of testosterone and androstenedione Irregular menstrual cycles [94][95][96] Raised expression of Receptor of AGE (RAGE) in mononuclear cells along with increased glucose, insulin, and testosterone PCOS characterized as both endocrine metabolic disorders [71,95,97] High AGE diet elevates anti-MĂŒllerian hormone, inhibits Follicle-stimulating hormone Provokes anovulation [98,99] High AGEs isocaloric diet elevates testosterone, insulin, and oxidative stress contributing to PCOS and its symptoms Irregular menstrual cycles, high ovarian cysts [92,97,100] Upregulation of RAGE in PCOS, downregulation signal cascade of steroidogenesis in women of reproductive age Disruptive hormone formation [91,101] Vitamin D3 supplementations reduce the effects of AGEs in PCOS Attenuates AGEs and supports ovarian health [102,103] Excess deposition of collagen Cyst formation in ovaries due to enzyme lysyl oxidase [102,104,105] Disruption of renin-angiotensin-aldosterone system Disturbed cardiovascular functioning and hypertension [37,106,107] Another study reported the association of a high AGE isocaloric diet (HA) with PCOS in women. Women consuming a high HA diet had elevated levels of serum AGEs, testosterone, insulin, and oxidative stress, as compared to women on low AGE isocaloric diet.…”
Section: Ages and Women's Healthmentioning
confidence: 99%
“…Immunostaining of COLI and IV have confirmed the increased expressions of these proteins in IUA horns (Figure 3(D,F)). Matrix metalloproteinases (MMPs) are zinc‐dependent endopeptidases that degrade different components of the ECM and play a role in the remodeling of various tissues during many physiological processes, including decidualization of stromal cells and postpartum uterine repair 29,30 . We found that the expression of Mmp2 and Mmp9 increased 6 and 9 days after the IUA surgery (Figure 3(E)), suggesting rapid ECM remodeling during this period.…”
Section: Resultsmentioning
confidence: 87%
“…Matrix metalloproteinases are important for uterine tissue remodeling and collagen degradation in uterus (Endo et al., 2006). To uncover the inner mechanism behind AM‐mediated protection, the expressions of various MMPs and TIMP‐1 were analyzed (Figure 6).…”
Section: Resultsmentioning
confidence: 99%